Pengabdian Pertanian Penanaman Cabai Guna Meningkatkan Ketahanan Pangan di Desa Rantau Panjang Kiri - Alnifa Zahra; Despita Putri; Eka Nuraini Mulya; Fauzan Haq Harahap; Muhammad Farih Azzaki; Nailam Aliah Mujahatul Ummah; Riski Afnanda; Sela Gustia Rani; Stella Andriani Rizka; Viskar Nugraha (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2024)
This community service program was conducted in Rantau Panjang Kiri Village, Riau, with the goal of enhancing food security through chili cultivation as the main commodity. The village faces significant challenges in food security due to heavy reliance on rice as the staple crop, making it vulnerable to climate change and market price fluctuations. To address these issues, training and mentoring were provided to farmers to develop their skills in sustainable chili cultivation. The program involved a series of phases including socialization, practical training, and evaluation. Socialization aimed to provide a basic understanding of the importance of crop diversification, while hands-on training focused on chili cultivation techniques, ranging from seed selection and land preparation to pest and disease control. Evaluation was conducted to measure the improvement in participants' knowledge and skills, as well as the impact of the program on chili production in the village. The results of the program showed a significant increase in farmers' understanding and skills regarding chili cultivation, as well as an increase in harvest yields, which helped strengthen the village's food security. Additionally, the program successfully raised farmers' awareness of the importance of optimal land use and reduced dependency on rice. Thus, this community service program not only supports local food security but also improves farmers' economic welfare through agricultural commodity diversification.